Incidence of workـ related eye injuries in miners between 2003 and 2008 - M Malek; MS Attarchi; M Aghilinejad; S Mohammadi; Z Sadeghi; S Khodadian (طب کار)
Abstract Background: Workـ related traumas could involve thousands of workers worldwide, especially in developing countries. These injuries may lead to incapacitation of work forces and ultimately impose a large economic load on industry. Due to the lack of statistics about the orbital trauma incidence among Iranian workers, we decided to evaluate the effects of age on the incidence of the ophthalmic trauma. Methods: In a retrospective descriptive study, all medical files of the miners between 2003 and 2008 were assessed, and workـ related injuries were recorded. These with ophthalmic trauma entered the study. Finally the relationship between age and incidence of the trauma was evaluated. Chi- square was used for analysis. Results: From 7100 occupational accidents, 377 cases (5.3%) suffered from ophthalmic trauma. Ophthalmic trauma had been most frequently occurred among 50-59 year old. Subjects (25.3%) and subjects under 20 years old were the second group (20.4%). The lowest frequency observed in subjects older than 60 year old. These wasn't any statistically significant difference in the frequency of ophthalmic injuries in different years (P>0.05). Accidents had been occurred mostly in the summer and between 8-10 A.M. Chi-square analysis showed a significant association between the age and frequency of trauma among miners (P<0.05). Conclusion: More frequent ophthalmic trauma in aforementioned age groups may be due to lower physical strength in older ages and lower job experience in year ages. These were no reduction in the frequency of trauma in different years which may be due to failure in the development of safety in the workplace.